Immune Control of AIDS Progression by an Adenovirus‐Based Therapeutic Vaccination in Acute Simian Immunodeficiency Virus‐Infected Macaques - Yizi He; Chunxiu Wu; Fengling Feng; Zijian Liu; Xugang Zhang; Qing Yang; Zhe Chen; Minjuan Shi; Ziyu Wen; Yichu Liu; Fengyu Hu; Linghua Li; et al. (MedComm)
ABSTRACT Therapeutic vaccinations that enhance human immunodeficiency virus (HIV)‐specific immunity hold promise for reducing reliance on antiretroviral therapy (ART). We previously developed an adenovirus vector‐infected peripheral blood mononuclear cell (AVIP) as a prophylactic strategy that enhanced cellular immunity in macaques and significantly reduced set‐point and peak simian immunodeficiency virus (SIV) loads following SIV challenge. However, its therapeutic efficacy remains to be fully explored. In this study, we improved AVIP by enhancing adenovirus entry into peripheral blood mononuclear cells (PBMCs) through in vitro co‐incubation with granulocyte‐macrophage colony‐stimulating factor (GM‐CSF). We constructed adenoviruses carrying SIV group‐specific antigen (Gag), envelope (Env), and polymerase (Pol) and evaluated the therapeutic potential of autologous AVIP infusion in acute SIV‐infected macaques. Compared with ART alone, AVIP in combination with ART elicited robust cellular immunity against SIV, effectively controlled SIV replication during ART, and delayed viral rebound and acquired immunodeficiency syndrome (AIDS) progression after ART discontinuation. Notably, 80% of macaques in AVIP+ART group maintain plasma virus control for at least 100 days after ART interruption. This sustained viral control is associated with vaccine‐induced Pol‐specific immune responses and reduced CD38 expression on CD8+ T cells. These findings support further investigation of AVIP as a therapeutic strategy against acute HIV infection.